A systematic review and meta-analysis of return to work after mild Traumatic brain injury. (6th December 2018) - Bloom, Ben; Thomas, Stephen; Ahrensberg, Jette Møller; Weaver, Rachel; Fowler, Alex; Bestwick, Jon; Harris, Tim; Pearse, Rupert
ABSTRACT: Objective: To perform a systematic review and meta-analysis of return to work (RTW) times for adult patients with mild traumatic brain injury (mTBI). Methods: Six databases and six trials registries were searched. Inclusion: studies reporting RTW, > 30 patients, adults, with mTBI. Exclusion: final measurement RTW < 30 days after injury, first measurement > 1 year. Results: Of 978 records, 14 eligible studies were identified. Two included patients exclusively in paid employment pre-injury; four included paid employment, students, homemakers or other activities; seven included pre-injury occupational status described but unclear; one included patients whose pre-injury occupational status not described. Three reported average RTW, 12 reported proportions of patients RTW at pre-specified time-points (1 both). Average RTW times varied from 13 to 93 days. At 1 month the proportion of patients RTW (three pooled studies) was 0.56 (95% CI 0.30–0.79), at 6 months (six studies) 0.83 (0.74–0.89), at 12 months (seven studies) 0.89 (0.83–0.93). Conclusion: More than half of patients with mTBI have returned to work by 1 month after injury, and more than 80% by 6 months. Most studies had poor internal validity. Reporting of outcomes in mTBI is variable, and this accounted for some of the heterogeneity found in this review.